Cardiac remodelling with endurance exercise - Levine, B. (The Journal of Physiology, 2003)
Cross-sectional studies have demonstrated that endurance athletes have `eccentric hypertrophy` of the heart with increased mass and volume. The functional consequence of this adaptation is a more compliant, distensible left ventricle, which operates on the steep portion of the Starling curve, facilitating a large increase in stroke volume during exercise by the Frank-Starling mechanism. However, whether this phenotype is truly in direct response to endurance training, or rather is a unique characteristic of individuals destined for athletic success in endurance sport is not clear. As part of this symposium, I will present the results of a novel investigation in which a group of previously sedentary young men and women trained for a year to compete in a marathon, using training techniques typically followed by elite athletes. The results challenge conventional thinking regarding the morphologic response to endurance training. During the early phases of the training programme there was eccentric right ventricular hypertrophy, but concentric left ventricular hypertrophy, characterized by an increase in mass and wall thickness with only a minimal increase in volume. It was not until very prolonged training sessions, as well as highintensity interval training was incorporated into the training programme that eccentric hypertrophy of the LV developed. Although after 1 year of training, Starling curves approached those observed with elite athletes, LV pressure volume curves did not achieve the same compliance as those observed crosssectionally in elite athletes. There were remarkable gender differences as well, with females demonstrating substantially less hypertrophy than males, despite identical training regimens. Finally, comprehensive studies in our laboratory involving a wide range of physical activity (from 12 weeks of bed rest to 1 year of training) demonstrate that a remarkable 37 % of the mass of the LV is plastic, and adaptable with changes in exercise training.